2009
DOI: 10.1152/japplphysiol.91256.2008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia increases left ventricular contractility in C57BL/6J mice

Abstract: Intermittent hypoxia (IH) commonly occurs in patients with obstructive sleep apnea and can cause a wide range of pathology, including reduced left ventricular (LV) ejection fraction in rats as determined by echocardiography, in rodent models. We utilized echocardiography and pressure-volume (PV) loop analyses to determine whether LV contractility was decreased in inbred C57BL/6J mice exposed to IH and whether blockade of beta-adrenergic receptors modified the response to hypoxia. Adult male 9- to 10-wk-old mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 40 publications
6
48
1
Order By: Relevance
“…Signaling via the β 2 -adrenergic receptor (β 2 -AR) coordinates hypoxic adaptation across multiple organs, including the lungs (improved ventilation/perfusion matching) (38)(39)(40)(41), skeletal muscle (hypoxic vasodilation [HVD]) (41)(42)(43), and heart (augmenting contractility) (44). Through its influence on β 2 -AR signaling, S-nitrosylation may regulate hypoxic responses.…”
mentioning
confidence: 99%
“…Signaling via the β 2 -adrenergic receptor (β 2 -AR) coordinates hypoxic adaptation across multiple organs, including the lungs (improved ventilation/perfusion matching) (38)(39)(40)(41), skeletal muscle (hypoxic vasodilation [HVD]) (41)(42)(43), and heart (augmenting contractility) (44). Through its influence on β 2 -AR signaling, S-nitrosylation may regulate hypoxic responses.…”
mentioning
confidence: 99%
“…It is probable that moderate hemodynamic stress reduces the levels of inflammatory markers and increases flow-mediated vasodilation by ischemic preconditioning. In patients with CAD, it has been shown that increased walking ability is associated with improved LVEF [14,15] . The recently published study of Bøtker et al [16] has provided a promising result, showing that RIPC before hospital admission in the setting of ACS protects LV function.…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of ROS has been explained as depending on concentration, such that ROS emerge as cardioprotective at low levels but detrimental at high levels (36,165). In support of such assumptions, Naghshin and colleagues (118,119) reported that chronic IH treatment is sufficient to improve cardiac function in healthy mice and transgenic mice with underlying heart failure.…”
Section: Whenmentioning
confidence: 99%